Soil dynamic alterations and use efficiency of nitrogen by Brachiaria species - Castoldi, Gustavo; dos Reis, Jhônatas Gomes [UNESP]; Freiberger, Mariângela Brito; Santos, Darliane de Castro; Rosolem, Ciro Antonio [UNESP] (Southern Cross Publishing, 2017)
Under certain circumstances species of the Brachiaria genus, particularly B. humidicola might be able to suppress the biological nitrification in soil. This study aimed to investigate the ability of four Brachiaria species cultivated in Brazil to promote changes in the N dynamics in the soil as well as its capacity in use efficiently N under low N availability. In a greenhouse condition and using a Quartzipsamment soil, four species of Brachiaria (B. brizantha, B. decumbens, B. humidicola and B. ruziziensis) and two cut managements (single cut - performed at 140 days after seeding (DAS) and cut/regrowth- performed at 55 DAS and 85 days after the first cut (140 DAS)), plus a control treatment containing only soil were compared in a factorial design (4×2+1). The following evaluations were performed in plants: dry matter of shoots and roots, total N content, N accumulated and N use efficiency; and soil (which was split in rhizospheric and non-rhizospheric): ammonium, nitrate and total-N contents and pH value. Based on the soil inorganic-N content, there was no detectable effect of species in the soil nitrification process. Moreover, the highest ability of uptaking and using the N was observed in B. humidicola, which in the single cut management proved to be able to produce 201 g of shoot dry matter in response to each 1 g of N accumulated.
Keywords: Brachiaria brizantha; Brachiaria decumbens; Brachiaria humidicola; Brachiaria ruziziensis; Nitrification